Space exploration and astronaut safety - Pelton, Joseph N.; Marshall, Peter (American Institute of Aeronautics and Astronautics, 2006)
Reviews the history of NASA's space exploration program, its astronaut safety program, the status of the Space Shuttle and the International Space Station, and the options and strategic opportunities. This book presents the state of space technology, along with the concerns about safety in space exploration.